Hawaiki, ancestral Polynesia an essay in historical anthropology - Kirch, Patrick Vinton 1950- (Cambridge University Press, 2001)
The power of an anthropological approach to long-term history lies in its unique ability to combine diverse evidence, from archaeological artifacts to ethnographic texts and comparative word lists. In this innovative book, Kirch and Green explicitly develop the theoretical underpinnings, as well as the particular methods, for such a historical anthropology. Drawing upon and integrating the approaches of archaeology, comparative ethnography, and historical linguistics, they advance a phylogenetic model for cultural diversification, and apply a triangulation method for historical reconstruction. They illustrate their approach through meticulous application to the history of the Polynesian cultures, and for the first time reconstruct in extensive detail the Ancestral Polynesian culture that flourished in the Polynesian homeland - Hawaiki - some 2,500 years ago. Of great significance for Oceanic studies, Kirch and Green's book will be essential reading for any anthropologist, prehistorian, linguist, or cultural historian concerned with the theory and method of long-term history